Prognostic value of disease-free interval in colorectal cancer: Is it time? - Birgin, Emrullah; Doyon, Fabian; Burkert, Justin Lukas; Téoule, Patrick; Rasbach, Erik; Rahbari, Mohammad; Reißfelder, Christoph; Betzler, Alexander; Rahbari, Nuh Nabi (European journal of surgical oncology, 2022)
Background - Previous studies have outlined that the onset of synchronous colorectal cancer (CRC) metastases is associated with poor overall survival (OS) compared to patients with metachronous disease. The aim of this study was to evaluate the association of disease-free interval with newly diagnosed CRC scheduled for primary tumor resection. - Methods - Patients who underwent primary CRC resection over an 18-year period were identified from a prospective database at a tertiary-care hospital. In this observational study, the cohort was stratified for the onset of metastases, i.e. synchronous, early-onset and late-onset metachronous disease. The OS was compared using Kaplan-Meier estimators and stratified Cox hazard regression analysis. - Results - Of 360 patients, 204 (57%) had synchronous, 61 (17%) had early metachronous, and 95 (26%) had late metachronous metastases, respectively. The onset of synchronous metastases was not associated with worse OS compared to early and late metachronous disease. ASA level > II (P = 0.011), right-sided compared to left-sided cancer (P = 0.032) or rectal cancer (P < 0.001), and high-grade tumors (P = 0.022) were identified as independent predictors of poor OS, whereas the only favorable prognostic factor was surgical resection of metastases (P = 0.047). Additionally, ASA level < III (P = 0.003) and low-grade tumors (P = 0.032) were found to predict resection of metastases. - Conclusion - Individual patients' and tumor characteristics rather than the timing of metastases are associated with OS in newly diagnosed CRC. These data support curative treatment strategies even in patients with synchronous metastases.
Online verfügbar: 3 June 2022, Artikelversion: 26 September 2022
Gesehen am 18.09.2023